Entrepreneurial Intentions for Green Entrepreneurial Behavior in the Context of Universities in Jiangxi China: An Assessment of Entrepreneurial Endorsement and University Educational Support - Shenmiao, Han; Kamruddin, Badrul Hisham bin (South Asian Journal of Social Sciences and Humanities, 2024)
Background and Purpose: Green entrepreneurship has gained significant attention all over the world due to its contribution towards ecological and environmental protection. The present study investigates the impact of the entrepreneurial mindset (EM) and entrepreneurial intentions (EI) on green entrepreneurial behavior (GEB) within the context of universities in Jiangxi, China, by focusing on the mediating role of entrepreneurial endorsement (EE) and the moderating role university educational support (UES). Method: The present study is based on a quantitative research design and utilized a survey questionnaire for data collection. The population for the study consisted of student entrepreneurs from the selected universities in Jiangxi, China. The study used a purposive sampling strategy, and 330 complete responses were obtained. The data was analyzed through the application of PLS-SEM. Findings: The statistical analysis of the quantitative data revealed that EI and EM had a positive and significant impact on nurturing GEB in university students. However, UES was found to be an insignificant moderator in the association between EM and GEB, and EI and GEB. Additionally, the study supported the mediating role of EE in the association between EM and GEB while the relationship between EI and GEB was also significantly mediated by EE. Conclusion and Implications: Thus, the present study affirmed the significance of educational institutes for enhancing the GEB in university students. The findings of the study hold significance for the development of entrepreneurship curriculum in higher education in China, and also offers insights for practitioners in the educational sector for development of policies and environment which promotes entrepreneurship.